Nuances of COVID-19 and Psychosocial Work Environment on Nurses’ Wellbeing: The Mediating Role of Stress and Eustress in Lieu to JD-R Theory - Meirun, Tang; Bano, Sobia; Javaid, Muhammad Umair; Arshad, Muhammad Zulqarnain; Shah, Muhammad Umair; Rehman, Umair; Parvez, Zar Ayesha; Ilyas, Muhammad (Frontiers in Psychology, 2020)
Abstract Background: Global spread of COVID-19 makes Pakistan as vulnerable as any other developing country and the risk for weak health system increments the fears in the people’s minds. The government is strategically aligning expanded scope of community ownership and understanding in the population through risk communication and engagement; still, the situation looks very austere and even affects the psychological health of caregivers. We, therefore, sought to determine whether the impact of psychosocial job demands, and resources associated with the psychological health of the nurses in time lag duration of three months i.e. since the start of the pandemic from January to March 2020. We hypothesized the significant mediating roles of stress and eustress in the direct relationship of psychosocial work environment job demands, job resources, and nurse’s wellbeing. Methods: In this cross-sectional self-administrated study, we distributed the survey in two parts by using time-lag strategy to collect data at the start of pandemic (Time 1) and then three months later (Time 2). Data on 53 items was collected from 208 female nurses who have participated in both the time phases and met the eligibility protocols of study such as certified female nurses who have registration number (RN) through Pakistan Nursing Council (PNC), four years of generic nursing degree and two years of nursing experience. Findings: We have achieved three stages through our study analytic nurses’ sample to determine the predictive abilities for the quality of the psychosocial work environment model. The coefficient of determination R2, effect size ƒ2. We found 29.0% of the variance, 0.05 and 0.03 effect size, and 0.153 predictive abilities on stress as explained by job demands; 53.4% of the variance, 0.19 and 0.39 effect size, and 0.275 predictive abilities on eustress as explained by job resources. And finally, 71.2% of the variance, 0.00, 0.02, 0.02, 0.03, 0.42, and 0.07 effect sizes and 0.545 predictive abilities on our third endogenous construct wellbeing is explained by both the psychosocial job demands and job resources variables. From partial mediation to full, stress and eustress significantly impact the psychosocial work environment of nurses